2009
DOI: 10.1007/s10620-009-0870-9
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Small Intestinal Bacterial Overgrowth and Peripheral Bacterial DNA in Cirrhotic Patients

Abstract: SIBO in cirrhosis patients was observed at a very high frequency, and SIBO showed a high correlation with bacterial translocation, suggesting that SIBO could be a major risk factor of bacterial translocation, especially in ascitic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 20 publications
2
58
0
2
Order By: Relevance
“…Threemonth mortality was increased in the presence of ascitic bDNA only for patients with a MELD score > 15 [39] . Contrary to hospitalized patients, bDNA was rarely detected in ascitic fluid and serum of asymptomatic [20] , Francés et al [31] , El-Naggar et al [32] , González-Navajas et al [33] , Zapater et al [34] , Jun et al [35] , Fagan et al [36] Cons: Variable rates of detection (maybe depending on methodology used), lower prevalence in outpatients…”
Section: Bacterial Dnamentioning
confidence: 98%
See 1 more Smart Citation
“…Threemonth mortality was increased in the presence of ascitic bDNA only for patients with a MELD score > 15 [39] . Contrary to hospitalized patients, bDNA was rarely detected in ascitic fluid and serum of asymptomatic [20] , Francés et al [31] , El-Naggar et al [32] , González-Navajas et al [33] , Zapater et al [34] , Jun et al [35] , Fagan et al [36] Cons: Variable rates of detection (maybe depending on methodology used), lower prevalence in outpatients…”
Section: Bacterial Dnamentioning
confidence: 98%
“…The presence of bDNA was also associated with peripheral vasodilation and deterioration of intrahepatic endothelial function [20] . Another study highlighted the strong correlation between SIBO and the presence of bDNA in the peripheral blood of patients with cirrhosis [35] . Moreover, the high bDNA detection frequency was recently confirmed as it was shown that it was detected in ascitic fluid from 23 of 25 patients with culture-negative, non-neutrocytic ascites.…”
Section: Bacterial Dnamentioning
confidence: 99%
“…Gut flora imbalances and higher levels of Enterobacteriaceae resulted in significant changes in BT and liver function in cirrhotic rats [128]. Further, SIBO in cirrhosis showed a high correlation with the presence of bacterial DNA fragments in peripheral blood, suggesting that SIBO could be a major risk factor for BT, especially in ascitic patients [129]. …”
Section: Bacterial Translocationmentioning
confidence: 99%
“…Patients with cirrhosis, particularly those with decompensated disease, are at risk of developing serious bacterial infections due to several factors (1,2) ; such as, portal hypertension (3) , immunologic impairment (4) , quantitative and qualitative changes in gut microbiota, intestinal dismotility (5) , small intestinal bacterial overgrowth (6,7) . The gastric acidity is an important host defense barrier; therefore, acid suppression has been associated with adverse events; such as, enteric infections (8,9) , pulmonary infections (10,11) , development of bacterial intestinal overgrowth and bacterial translocation (7) .…”
Section: Introductionmentioning
confidence: 99%
“…The gastric acidity is an important host defense barrier; therefore, acid suppression has been associated with adverse events; such as, enteric infections (8,9) , pulmonary infections (10,11) , development of bacterial intestinal overgrowth and bacterial translocation (7) . Proton pump inhibitors (PPI) are frequently prescribed in patients with cirrhosis, but at least two studies have reported a high prevalence of patients taking acid-suppressive therapy without a clear indication (12,13) .…”
Section: Introductionmentioning
confidence: 99%